Comparative study of cobalt (ii) using 4-hydroxy 3, 5 dimethoxy benzaldehyde 4-hydroxy benzoyl hydrazone and cinnamaldehyde 4-hydroxy benzoylhydrazone in presence of micellar medium by spectrophotometry - D.GOPALA KRISHNA,; N.DEVANNA,; K.B.CHANDRASEKHAR, (International Journal of Pharma and Bio Sciences, 2011)
Two simple, sensitive, rapid and selective spectrophotometric methods have been developed for the determination of Cobalt (II) by using newly synthesized reagents 4-Hdroxy3, 5dimethoxy benzaldehyde-4hydroxybenzoylhydrazone (HDMBHBH) and Cinnamaldehyde 4-hydroxy benzoylhydrazone (CMHBH) in presence of neutral surfactant TritonX-100 (5%) (micellar medium). Cobalt (II) forms a yellow coluored water-soluble complex with HDMBHBH and CMHBH-in the pH range 9.0-12.0.The Co (II)-HDMBHBH complex shows maximum absorbance at λmax 397 nm in the pH range 8.0-9.0 and Co (II)-CMHBH shows at λmax 393 nm in the pH range 8.0-9.0. At these wavelengths (λmax), the complex shows maximum absorbance while the reagent blanks shows negligible absorbance. Hence, analytical studies were carried out at λmax 397 nm at pH 9.0 for HDMBHBH and 393 nm at pH 9.0 for CMHBH against reagent blanks. Beer's law is obeyed in the range 0.058-0.589µg ml-1 and the optimum concentration range from ringbom plot is 0.117-0.530 µg/ml for Co (II)-HDMBHBH, and 0.029-0.294 ml-1 , 0.058-0.265 for Co (II)-CMHBH. The molar absorptivity and Sandell's sensitivity for the coloured solution were found to be 4.37x 104 L mol-1 cm-1 and 0.0013-µg. cm-2 for Co (II)-HDMBHBH, 6.5 x 104 L mol-1 cm-1 , and 0.0009-µg. cm-2 for Co (II)-CMHBH respectively. The interference effects of various diverse ions have been studied. Co (II) forms 1:1 complex with HDMBHBH and 1:2 with CMHBH stoichiometry with stability constant 11.47x106 for Co (II)HDMBHBH and 3.07 x 1012 for Co (II)-CMHBH. The standard deviation in the determination of 0.117-µg ml-1 of Cobalt (II) is 0.002 for HDMBHBH and 0.0024 for CMHBH.The Relative standard deviation is 2.53% for Co (II)HDMBHBH and 2.3 % for Co (II)-CMHBH complex. First and second order derivative spectroscopic methods was developed at λmax 434 nm and 470 nm for Co (II)-HDMBHBH and at 440 nm and 463 nm for Co (II)-CMHBH, for the determination of Cobalt (II) which is more sensitive than the zero order method. The developed method has been used for the determination of Cobalt (II) in Tealeaves, Vehicle exhaust, alloy samples and in vitamin B12. The results are in good agreement with the certified values.